Determinant of Child Schooling in Indonesia - Losina Purnastuti (Jurnal Ekonomi dan Pendidikan, 2006)
Using the 1993 Indonesia Family Life Survey, this paper examines school participation among boys and girls in Indonesia and investigates why parents are less likely to keep their daughter in school. The analysis is based on indicators of school attendance. In particular we focus on the gender difference in school attendance, effect of parents education and employment, household resource constraint, location of the household and quality of the school. This paper finds significant gender differences in childrens education. Parents are more likely to send their sons to school rather than their daughters. Parents education has significant positive impact on their childrens schooling in different manner. Mothers education has stronger impact on girls school attendance, while fathers education has stronger impact on boys school attendance. Household income matters only for girls; it implies that girls belonging to poor families are less likely to go to school, and education is a luxury good for these girls. Further the number of children under 5 years old in the household also matters only for girls. This indicates that for girls there is a trade off between being in school and taking care of younger siblings as well as substituting for the mother in doing domestic tasks.